"Falter Not in Practising Tenderheartedness": Notes on Political Subjectivity in Contemporary Russian Poetry. (3rd July 2018) - Maiofis, Maria
Abstract : In "Falter Not in Practicing Tenderheartedness, " Maria Maiofis argues that the political sphere does not lose autonomy in poetry by the "generation of the 1990s, " since different realities are acquiring primary significance. Contemporary poetry's reaction to political events is an indispensable part of a wider lyrical reaction of the author/hero who seeks involvement and participation in global events. Maofis concludes by comparing this tendency to the writing of Aleksandr Radishchev.